Advancing full length genome sequencing for human RNA viral pathogens. (January 2009) - Djikeng, Appolinaire; Spiro, David
In the face of numerous emerging and re-emerging viral threats, large-scale genome sequencing efforts are underway to monitor viral evolution in real-time. To fully appreciate the mechanisms of viral adaptation and evolution, and to also develop reagents and resources for a better molecular diagnosis of emerging and re-emerging viral infections, there has been an increasing effort toward producing full length viral genome sequences. To date, high-throughput platforms have been developed using traditional Sanger-based sequencing and there are currently prospects to apply next generation sequencing methods to develop an ultra high-throughput strategy for viral genome sequencing and analysis.